Optimization of Services and Accessibility Webinar Tutorials on Satisfaction Using the Microsoft Teams Application for Universitas Terbuka Students - Amud Sunarya; Florentina Ratih Wulandari (Ilomata International Journal of Social Science, 2023)
This research aims to determine the effect of webinar tutorial facilities and accessibility on student satisfaction in applying Microsoft Teams. This type of research is survey research that is quantitative with multiple linear regression analysis. Where the service and accessibility of the webinar tutorial are independent variables, and student satisfaction with using the Microsoft Teams application is the dependent variable. The research population is the Universitas Terbuka students in the 2022.2 academic year who follow the webinar tutorial for scientific papers. Obtained the sample from students of the public administration study program by filling out google forms. This study tries to show a positive influence between the service and accessibility of webinar tutorials on student satisfaction after applying Microsoft Teams. The study is expected to produce new findings on the benefits and accessibility of webinar tutorials to provide satisfaction to Universitas Terbuka students in using the Microsoft Teams application.